Multi-Physical Field Coupling Analysis of Electro-Controlled Permanent Magnet Blank Holder Processes Considering Thermal Magnetic Losses - Zhanshan Wang; Linyuan Meng; Gaochao Yu; Xiaoyu Ji (Metals)
Electro-permanent magnet (EPM) technology is characterized by high integration, strong modularity, and stable magnetic force, making it a current research focus when combined with sheet metal deep drawing processes to develop EPM blank holder deep drawing technology. In this study, we investigated the issue of thermal magnetic quantitative magnetic loss after the prolonged use of the EPMBH process, analyzing the variation in magnetic force with the temperature increase to provide necessary data support for the application of the EPMBH. First, a thermal network model for the four-magnetic pole unit EPM magnetic device was established, and through calculations on this model, the thermal equilibrium temperatures for the permanent magnet (PM)-NdFeB and reversible magnet (RM)-AlNiCo were found to be 72.13 °C and 72.41 °C, respectively. Second, the magnetic performance of PM and RM at different temperature points was measured to analyze the variation in their magnetic characteristics with the temperature increase. Third, a magnetic force model of the EPM magnetic device was established, and finite element analysis was conducted using the measured magnetic characteristics data of RM and PM. The results indicated that an increase in temperature leads to a reduction in magnetic force, with a maximum reduction of 18.57% observed after thermal equilibrium. An experimental testing platform was designed and built to validate the calculation and simulation results. Finally, a sheet metal deep drawing experiment using the EPMBH process was conducted, taking into account thermal magnetic loss factors. The results showed that magnetic force loss due to temperature rise affects the forming quality of the sheet metal. Therefore, in practical applications, it is necessary to establish a real-time temperature monitoring system and develop a temperature-based magnetic force compensation module.